Polyfunkční dům - Šrejma, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Předmětem této diplomové práce je návrh polyfunkčního domu ve městě Zábřeh v okresu Šumperk. Dům je nepodsklepený. Je rozdělen na dvě provozní části – komerční prostory a prostory pro bydlení. Objekt má čtyři nadzemní podlaží. Nosné svislé konstrukce tvoří keramický systém Porotherm, vodorovné nosné konstrukce jsou tvořeny keramickými vložkami systému Porotherm. Objekt je zastřešen plochou střechou.

The aim of this diploma thesis is design of multifunctional building in the town Zábřeh in dis-trict Šumperk. The house is no basement. It is divided into two operating parts – commercial space and residential space. The building has four floors. Vertical supporting structure are formed by ceramic system Porotherm, horizontal supporting structures are formed by ceramic inserts Porotherm. The building is covered with a flat roof.
Multifunctional Building
Keywords: Polyfunkční dům; objekt pro bydlení; objekt pro veřejnost; zděná budovy; Porotherm; Miako; novostavba; plochá střecha; terasa; zelená střecha; mezonetový byt; Multifunctional building; building for housing; building for the public; masonry building; Poro-therm; Miako; new building; flat roof; terrace; green roof; maisonette